Processo de eletrocoagulação aplicado ao tratamento de água residuária sintética contendo o contaminante emergente furosemida - Silva, Larissa Botura da (2025)
The growing concern for the preservation of water resources has driven studies on the presence and removal of emerging pollutants, such as pharmaceuticals, from water bodies. Among these compounds, furosemide, a widely used diuretic, has been detected in wastewater due to its low degradation in conventional treatment processes. Therefore, several technologies have been studied for its removal, with electrocoagulation being a promising alternative. This process is based on the in situ generation of coagulating agents from the electrolytic oxidation of metal electrodes, promoting the destabilization and removal of pollutants. This study investigated the efficiency of electrocoagulation in the removal of furosemide from a synthetic effluent, using aluminum electrodes. The experiment was conducted in batch mode, varying three main parts: the distance between the electrodes (1.0 cm; 1.5 cm; and 2.0 cm), the contaminant concentration (0.1 mg/mL; 0.2 mg/mL; and 0.3 mg/mL) and the applied voltage (1.0 V; 2.0 V; and 3.0 V). The efficiency of furosemide removal, particle size, zeta potential, electrode saturation time and operational cost of the process were evaluated. The tests demonstrated that the highest removal efficiency, up to 66,0%, was obtained with electrodes spaced 1.5 cm apart, concentration of 0.3 mg/mL and voltage of 3.0 V. Through statistical analysis it was possible to verify that the only variable that significantly influenced the removal efficiency was the furosemide concentration. The analysis of the zeta potential revealed a reduction in the electrostatic repulsion between the particles, favoring coagulation and the formation of sedimentable flocs. This fact could be confirmed by analyzing the particle size, which increased throughout the treatment, confirming the aggregation of the flocs promoted by electrocoagulation. In addition, it was observed that smaller distances between electrodes result in greater energy consumption, while larger spacings reduce the efficiency of the treatment. The cost analysis indicated that electrocoagulation may be economically viable, provided that operational parameters are optimized. The results confirm the potential of electrocoagulation as an efficient alternative for the removal of pharmaceuticals from effluents, contributing to the reduction of the environmental impact caused by emerging contaminants.